Geomorphology of a thermo-erosion gully, Bylot Island, Nunavut, Canada 1 This article is one of a series of papers published in this CJES Special Issue on the theme of Fundamental and applied research on permafrost in Canada. 2 Polar Continental Shelf Project Contribution 043-11. - Godin, Etienne; Fortier, Daniel (Canadian Journal of Earth Sciences, 2012)
A thermo-erosion gully has been monitored in the valley of glacier C-79 on Bylot Island since 1999. The main channel of the gully reached 390 m in length a few months after its initiation and grew between 38 and 50 m/year over the following decade, for an overall approximated average of 75 m/year. In 2009, the total gully length and area, including the main and relict channels, were 2500 m and 25 000 m 2 , respectively. Gullies affect snow accumulation, and therefore ground temperature, local water flow, and drainage. Sinkholes, gully heads, pools, baydzherakhi, tunnels, and collapses were grouped as a function of time since gully formation in that area. Sinkholes and tunnels were formed every year after gully inception, and baydzherakhi were found in 3–10 year old sections of the gully. Stabilization of the gully floor and sides took about a decade.